Therapeutic Hypothermia for Refractory Status Epilepticus. (10th June 2015) - Zeiler, Frederick A.; Zeiler, Kaitlin J.; Teitelbaum, Jeanne; Gillman, Lawrence M.; West, Michael
Abstract Background : Our goal was to perform a systematic review of the literature on the use of therapeutic hypothermia for refractory status epilepticus (RSE) and its impact on seizure control. Methods: All articles from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to May 2014), reference lists of relevant articles, and gray literature were searched. The strength of evidence was adjudicated by two independent reviewers, using both the Oxford and GRADE methodology. Results: Overall, 13 studies were identified, with 10 manuscripts and 3 meeting abstracts. A total of 40 patients were treated. The common target temperature was 33 degrees Celsius, sustained for a median 48 hours. Patients displayed a 62.5%, 15% and 22.5% rate of seizure cessation, seizure reduction, and failure of treatment respectively. External cooling was utilized in the majority of cases. Deep venous thrombosis, coagulopathy and infections were the commonly reported complications. Two ongoing clinical trials were identified. Conclusions: Oxford level 4, GRADE D evidence exists to support the use of therapeutic hypothermia to control seizures in RSE. Further prospective study is warranted.